1999
DOI: 10.1002/(sici)1098-2337(1999)25:4<269::aid-ab3>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Development of social problem‐solving strategies and changes in aggressive behavior: A 7‐year follow‐up from childhood to late adolescence

Abstract: The aim of this study was to predict a stability of aggressive behavior on the basis of social problem-solving strategies. Subjects were a total of 120 children, but complete follow-up data were available only in 47 cases. Their aggressive behaviors were peer rated, and problem-solving strategies were assessed in childhood subjects being 10 years on average, and 7 years later. Association between a development of social strategies and changes in aggressive behavior was studied with personality-oriented pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This movement was consistent with the strategies used, i.e. the girls who in childhood used withdrawing instead of aggressive strategies, but used aggressive strategies in late adolescence, also behaved aggressively in adolescence (see Table 1; for details, see Keltikangas-Järvinen and Pakaslahti, 1999).…”
Section: Changes In Social Problem-solving Strategies As Predictors Osupporting
confidence: 73%
See 1 more Smart Citation
“…This movement was consistent with the strategies used, i.e. the girls who in childhood used withdrawing instead of aggressive strategies, but used aggressive strategies in late adolescence, also behaved aggressively in adolescence (see Table 1; for details, see Keltikangas-Järvinen and Pakaslahti, 1999).…”
Section: Changes In Social Problem-solving Strategies As Predictors Osupporting
confidence: 73%
“…The type of problem solving used in childhood did not predict problem solving in late adolescence, not even in solving similar problems (for details, see Keltikangas-Järvinen and Pakaslahti, 1999).…”
Section: Stability Of Behaviour and Problem-solving Strategiesmentioning
confidence: 99%
“…There is abundant evidence of an association between social problem-solving deficits and problems related to PD. [24][25][26][27] People with PD report less desirable scores on all scales of the Social Problem-Solving Inventory -Revised: Short Version (SPSI-R) 28 compared with a sample of mature students, 22 and people high on borderline traits show poorer social problem-solving abilities than those with lower borderline traits, particularly when experiencing negative emotions. 29 This information suggests that social problem-solving therapy may benefit people with PD.…”
Section: Social Problem-solving Therapymentioning
confidence: 99%
“…With regards to the relationship between constructive conflict resolution and aggression, it has been observed that aggressive children and teenagers behaved more destructively and violently when faced with interpersonal conflicts and had more aggressive problem solving options in their social-cognitive memories (Lochman and Dodge, 1994;Pakaslahti and Keltikangas-Järvinen, 1996;Crick and Dodge, 1994;Huesmann, 1988), while non-aggressive children and teenagers found collaborative and friendly solutions (Lochmann & Dodge, 1994). According to the findings of a longitudinal study, aggressive children and teenagers use aggressive problem solving strategies (Keltikangas-Järvinen & Pakaslahti, 1999).…”
Section: The Relationship Between School Attachment Constructive Conmentioning
confidence: 99%